ANALISIS YURIDIS TERHADAP PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA PENGGELAPAN DALAM JABATAN (STUDI PUTUSAN No. 164/Pid.B/2018/PN MKS) - Octavia, Andi Rizky (Equality Before The Law, 2022)
This article is a juridical research on the accountability of criminal offenders through the study of court decisions. This research was born due to the inaccuracy of the demands submitted by the public prosecutor who did not think about the deterrent effect on the perpetrators. The research method used by the researcher is based on the applicable legislation by looking at the case being litigated. There are two objectives of the research, namely to find out the indictment of the public prosecutor against the crime of embezzlement in office and how the judge's considerations in imposing the sentence in decision number 164/Pid.B/2018/PN.Mks. The results showed that the Public Prosecutor in making the indictment was appropriate and appropriate, namely using a single indictment in Article 374 of the Criminal Code. According to the researcher, the charge was too light for the defendant because the victim in this case suffered a lot of losses. And the judge's consideration in his decision against the defendant was not quite right because the sentence handed down was only one year in prison while there were many things that the judge had to consider before imposing his sentence because the defendant was proven legally against the law.